2021
DOI: 10.1515/ntrev-2021-0098
|View full text |Cite
|
Sign up to set email alerts
|

Physical, thermal, and mechanical properties of highly porous polylactic acid/cellulose nanofibre scaffolds prepared by salt leaching technique

Abstract: This study aimed to prepare and characterise polylactic acid (PLA) reinforced with cellulose nanofibre (CNF) from a Pennisetum purpureum-based composite scaffold and determine its structural and mechanical properties. Porous scaffolds with CNF compositions of 5‒20 wt% in the PLA matrix were developed using solvent casting and particulate leaching of its porogen at 90 wt% of loadings. Morphology studies using field emission scanning electron microscopy revealed that the scaffolds had well-interconnected pores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Moreover, the porosity of the scaffolds was substantially influenced by the grafting process. Porosity represents the percentage of void space and is calculated by dividing the volume of voids by the total volume [ 26 ]. In tissue engineering, porosity and pores interconnectivity are extremely important as they facilitate cell attachment and proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the porosity of the scaffolds was substantially influenced by the grafting process. Porosity represents the percentage of void space and is calculated by dividing the volume of voids by the total volume [ 26 ]. In tissue engineering, porosity and pores interconnectivity are extremely important as they facilitate cell attachment and proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The total porosity of scaffolds was determined by the gravimetric method, as described in the previous literature [ 34 , 35 ]. Five specimens from each group were weighed in air and results recorded as m 0 .…”
Section: Methodsmentioning
confidence: 99%
“…In comparison, the scaffolds fabricated in this study demonstrated a higher compressive modulus than the aforementioned studies. However, it was essential to maintain a balance between achieving an appropriate porosity range of 40% to 95% [28] to facilitate cell infiltration and nutrient transport and ensuring sufficient mechanical properties to support cell growth and maintain scaffold integrity, specifically, the compressive modulus of bone scaffolds should be in the range of 2 MPa to 10 MPa [46].…”
Section: Mechanical Properties Of the Scaffoldsmentioning
confidence: 99%